Probiotic Strain Lactobacillus casei BL23 Prevents Colitis-Associated Colorectal Cancer - Jacouton, Elsa; Chain, Florian; Sokol, Harry; Langella, Philippe; Bermúdez-Humarán, Luis G. (Frontiers in Immunology, 2017)
The gut microbiota plays a major role in intestinal health, and an imbalance in its composition can lead to chronic gut inflammation and a predisposition to developing colorectal cancer (CRC). Currently, the use of probiotic bacteria represents an emerging alternative to treat and prevent cancer. Moreover, consumption of these beneficial bacteria may also favorably modulate the composition of the gut microbiota, which has been described in several studies to play an important role in CRC carcinogenesis. In this context, the aim of this study was to assess the protective effect of oral treatment with Lactobacillus casei BL23, a probiotic strain well known for its anti-inflammatory and anti-cancer properties. First, CRC was induced in C57BL6 mice by a single intraperitoneal injection with azoxymethan (AOM, 8 mg/Kg), followed by four courses of dextran sodium sulfate (2.5%) in drinking water that were separated by an adjustable recovery period. At the time of sacrifice (day 46), tumor incidence, histological scores, and epithelial proliferation were determined in colon samples. Our results show that L. casei BL23 significantly protected mice against CRC development; specifically, L. casei BL23 treatment reduced histological scores and proliferative index values. In addition, our analysis revealed that L. casei BL23 had an immunomodulatory effect, mediated through the downregulation of the IL-22 cytokine, and an anti-proliferative effect, mediated through the upregulation of caspase-7, caspase-9, and Bik. Finally, L. casei BL23 treatment tended to counterbalance CRC-induced dysbiosis in mice, as demonstrated by an analysis of fecal microbiota. Altogether our results demonstrate the high potential of L. casei BL23 for the development of new, probiotic-based strategies to fight CRC.